Chamaecrista pauciflora (Fabaceae) a new species from the lowlands of the state of Tocantins, Brazil - Matos, Ramon Guedes [UNESP]; Souza, Alessandro Oliveira; Da Silva, Marcos Jose (Magnolia Press, 2019)
Taxonomic studies in the genus Chamaecrista based on botanical collections from its endemic area, detailed analysis of our own collections and of herbaria, and in specialized literature enabled the discovery of a new species in the State of Tocantins, Brazil. The new species Chamaecrista pauciflora is herein described, illustrated, assigned to Chamaecrista sect. Absus subsect. Absus ser. Rigidulae and compared with C. azulana and C. filicifolia. The geographical distribution, conservation status, period of flowering and fruiting, morphological relationships, and environmental preferences of the new species are also provided. Additionally, a key to the species of Chamaecrista ser. Rigidulae occurring in Tocantins is presented.
Keywords: Cerrado; endemism; flora; Jalapao; taxonomy